PENGEMBANGAN BAHAN AJAR E-BOOK BERBASIS 3D DAN VIDEO KONTEKSTUAL PADA MATERI MEKANIKA ANALITIK LAGRANGE - Ririn Solekhah; Nasyaa Zahrotul Jannah; Bayu Setiaji (Charm Sains: Jurnal Pendidikan Fisika, 2024)
Technological advances encourage the advancement of various aspects of life, including education. This era is synonymous with instant and visual things. So, in order to keep up with the times, the teaching materials used must be able to adjust to the characteristics of current students. Physics students find it difficult to understand Lagrange's mechanical material. Thus, research was carried out to develop 3D-based e-book teaching materials and contextual videos on Lagrange mechanics material which is expected to improve the thinking skills of physics students related to Lagrange mechanics. The method carried out is RnD with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). But. The research only focuses on the Analysis, Design, and Development stages. In addition, a feasibility test was carried out from Physics Education practitioners and 10 samples of Physics Education students. The results obtained show that 3D-based e-book teaching materials and contextual videos are feasible to be used to improve students' understanding of Lagrange mechanics material.